Subcallosal Cingulate Cortex Deep Brain Stimulation for Treatment-Resistant Depression: A Systematic Review - Sobstyl, Michał; Kupryjaniuk, Anna; Prokopienko, Marek; Rylski, Marcin (Frontiers in Neurology, 2022)
Background: Deep brain stimulation (DBS) is considered a relatively new and still experimental therapeutic modality for treatment-resistant depression (TRD). There is clinical evidence to suggest that stimulation of the subcallosal cingulate cortex (SCC) involved in the pathogenesis of TRD may exert an antidepressant effect. Aims: To conduct a systematic review current studies, including randomized clinical trials, open-label trials, and placebo-controlled trials, examining of SCC DBS for TRD in human participants. Method: A formal review of the academic literature was performed using the Medical Literature, Analysis and Retrieval System on-line (MEDLINE) and Cochrane Central Register of Controlled Trials (CEN-TRAL) databases. This systematic review was conducted in accordance with the PRISMA guidelines. Suitable studies were screened and assessed based on patient characteristics, clinical outcome, and adverse events related to DBS, as well as the stereotactic technique used to guide the implantation of DBS electrodes. Results: The literature search identified 14 clinical studies enrolled a total of 230 patients with TRD who underwent SCC DBS. The average duration of follow-up was 14 months (range 6–24 months). The response and remission rates at the last available follow-up visit ranged between 23–92 % and 27–66.7 %, respectively. Conclusions: The current results of SCC DBS are limited by the relatively small number of patients treated worldwide. Nevertheless, studies to date suggest that SCC can be a promising and efficacious target for DBS, considering the high response and remission rates among patients with TRD. The adverse events of SCC DBS are usually transient and stimulation-induced.